THE EFFICACY OF STRUCTURED DEFENSIVE TECHNIQUE TRAINING ON ENHANCING DEFENSIVE CAPABILITIES IN VOLLEYBALL AMONG NINTH-GRADE STUDENTS AT SMPN 1 KUTACANE - Davit Long Edisyah; Ladipin; Afrizal (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aimed to determine the effect of defensive technique training on the defensive skills in volleyball of 9th-grade students at SMPN 1 Kutacane. The research used an experimental method with a one-group pretest-posttest design involving 30 students. Over a period of three weeks, participants underwent a structured training program focused on fundamental defensive techniques such as digging, forearm passing, and blocking. The results demonstrated a substantial improvement in defensive performance, with the average score increasing from 49.5 in the pretest to 85.0 in the posttest. Statistical analysis using a paired sample t-test yielded a highly significant result (t = 55.64 > t-table = 2.045), leading to the rejection of the null hypothesis. These findings robustly indicate that the implemented defensive technique training was profoundly effective in enhancing the students' volleyball defensive skills. The study concludes that a systematic and focused approach to teaching defensive fundamentals is crucial for skill development in adolescent athletes.